PENGARUH PENGETAHUAN DEWAN TENTANG ANGGARAN TERHADAP PENGAWASAN APBD DENGAN AKUNTABILITAS, KOMITMEN ORGANISASI, DAN POLITICAL BACKGROUND SEBAGAI VARIABEL MODERATING (Studi Empiris pada DPRD Kabupaten Rokan Hilir periode 2014-2019) - Annisa Hapsari; Nur Azlina; Al azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to test and prove empirically the influence of the board knowledge about the budget on budget oversight with the accountability, organizational commitment, and political background as moderating variable. The population is on DPRD located in Rokan Hilir regency in 2017. The sample used as the respondents was taken by using sensus sampling method. The Questionnaires was distributed to 45 respondents, which can be processed is 42 questionnaire. Data analysis techniques to test hypotheses using simple linear regression analysis and moderated regression analysis (MRA) with SPSS 21.0. The results of the tests show that the board knowledge about the budget has significant affect on budget oversight. And result also prove the relationship between the board knowledge about the budget with budget oversight are moderated by the accountability, organizational commitment, and political background.Keywords : Knowledge, Controlling, Accountability, Organizational Commitment, Political Background